Sigmoid Volvulus Sebagai Salah Satu Penyebab Terjadinya Ileus Obstruksi - Asri Aprillya; Haris Setia Ampera Hutagaol (Lembaga Pengembangan Kinerja Dosen, 2024)
Sigmoid volvulus is an event in which a part of the intestine is twisted around the blood supply. This incident usually occurs in endemic areas which account for 13% to 42% of all intestinal disorders. The condition is most common in patients over 60 years of age and along with several risk factors. Presents with colic abdominal pain, nausea, vomiting, and constipation; Usually there is abdominal distension, tenderness with varying degrees. On plain radiography, the key to diagnosing sigmoid volvulus is the